Límites legales al derecho de propiedad: A propósito de los Bonos Edificatorios y construcciones sostenibles - Reátegui Pilco, Jorge (2023)
The property right is not absolute. Issues of national interest such as the conservation of the National Cultural Heritage can limit it. Based on this, this article deals with those benefits that property owners may have, through building bonds granted in their favor, in order to maintain their value. Thus, said bonds recognize the building right of the owner of the property, so that he/she can build additional square meters in another area within the district where the bond was granted.These building bonds also apply to sustainable buildings to promote their development within the same district. The article develops the concept and types of building bonds, their implications, the need for their application, and criticisms of said regulation.